The Modigliani Puzzle Revisited: A Note - Margarita Katsimi; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2017)
We estimate the relationship between investment and unemployment in order to explore whether the medium-term relationship emphasized by Franco Modigliani survived the recent Great Recession. Our results indicate that the relationship held up, both employment and investment fell although the estimated coefficient of investment is slightly smaller when the period 2000-2015 is added to the 1960-2000 period.
Keywords: J10; E20; 330; Modigliani puzzle; investment; unemployment; Great Recession